2016
DOI: 10.3928/01484834-20160615-09
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Concept Mapping: Visual Aids for Knowledge Construction

Abstract: Background Concept mapping is a visual representation of ideas that facilitates critical thinking and is applicable to many areas of nursing education. Computer-Assisted Concept Maps are more flexible and less constrained than traditional paper methods, allowing for analysis and synthesis of complex topics and larger amounts of data. Ability to iteratively revise and collaboratively create computerized maps can contribute to enhanced interpersonal learning. However, there is limited awareness of free software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Lastly, in selecting which software to use, it may be beneficial to explore several options (e.g., Xmind , MindMaple , CMap ), as the operating characteristics and technical capabilities differ between programs. There are many free options available, and comparison of the strengths and weaknesses is available elsewhere (Mammen, ). In Table , we provide specific mapping techniques and keyboard shortcuts for Xmind (n.d.) and MindMaple (n.d.), which are the two free programs we have found most useful.…”
Section: How To Develop a Digital Mapmentioning
confidence: 99%
“…Lastly, in selecting which software to use, it may be beneficial to explore several options (e.g., Xmind , MindMaple , CMap ), as the operating characteristics and technical capabilities differ between programs. There are many free options available, and comparison of the strengths and weaknesses is available elsewhere (Mammen, ). In Table , we provide specific mapping techniques and keyboard shortcuts for Xmind (n.d.) and MindMaple (n.d.), which are the two free programs we have found most useful.…”
Section: How To Develop a Digital Mapmentioning
confidence: 99%
“…Computerassisted concept mapping has been introduced as a more flexible means for producing concept maps and presents an opportunity for even greater diversity in delivering this tool to students using an online format. [25] Many students found that having the information presented in a relaxed setting with a facilitator who enjoyed the subject and was able to relate directly to their own experiences in the course made the information itself seem more approachable.…”
Section: Discussionmentioning
confidence: 99%
“…Since paper-based concept maps are two dimensional and have limited space, it is difficult to place all the possible relationships between concepts on them [9]. Computer-based concept mappings provide potential benefits for both students and educators by eliminating the limitations of the traditional paper-based concept maps [32,33]. The benefits of computer-based concept mappings are presented below:…”
Section: Computer-based Concept Mappingmentioning
confidence: 99%
“…us/), MindMup (http://www.mindmup.com/), FreeMind (http://freemind.sourceforge.net/wiki/ index.php/Main_Page), and Mindomo (https://www.mindomo.com/). These consist of multipurpose programs that enable the integration of digital data (web links, images, videos, articles) into the map [33].…”
Section: Computer-based Concept Mappingmentioning
confidence: 99%
See 1 more Smart Citation